2021
DOI: 10.3390/ijerph18073376
|View full text |Cite
|
Sign up to set email alerts
|

Educational and Employment Outcomes among Young Australians with a History of Depressive Symptoms: A Prospective Cohort Study

Abstract: The aim of this study was to investigate whether depressive symptoms reported during adolescence are associated with subsequent educational and employment outcomes, including whether experiences of depressive symptoms in adolescence are associated with higher exposures to adverse psychosocial job stressors among those who were employed in emerging adulthood. We used data from the Victorian arm of the International Youth Development Study (IYDS). Multiple logistic regression analyses were used to model the asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Previous studies reported similar findings, i.e. that depressive symptoms in late adolescence and/or young adulthood are associated with work outcomes [2,[7][8][9][10][11][12][13], but only a few have examined the timing of depressive symptoms [17,18]. In contrast to our findings, De Groot et al [17] and Narusyte et al [18] reported the effect of internalizing problems on having paid work, sickness absence and disability pension to be independent of the timing of these problems [17,18], whereas we found that the effect of depressive symptoms on the risk of being NEET depended on timing but with different time points for boys and girls.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Previous studies reported similar findings, i.e. that depressive symptoms in late adolescence and/or young adulthood are associated with work outcomes [2,[7][8][9][10][11][12][13], but only a few have examined the timing of depressive symptoms [17,18]. In contrast to our findings, De Groot et al [17] and Narusyte et al [18] reported the effect of internalizing problems on having paid work, sickness absence and disability pension to be independent of the timing of these problems [17,18], whereas we found that the effect of depressive symptoms on the risk of being NEET depended on timing but with different time points for boys and girls.…”
Section: Discussionsupporting
confidence: 66%
“…Depressive symptoms affect several labour market outcomes, including NEET status (Neither in Education, Employment nor Training) [1][2][3][4][5][6][7][8][9][10][11][12][13][14], which may be due to a negative effect of depressive symptoms on the level of energy, concentration and motivation [4]. Also, poor labour market participation may affect mental health negatively [6,14].…”
Section: Introductionmentioning
confidence: 99%
“…43 In France, there is a push for the construction and building refurbishment sectors to become increasingly greener. 44 This push for a greener construction and building refurbishment sectors was also seen in the UK. 45 Some interviewees also emphasised that there were various interpretations of the green economy.…”
Section: Local Green Jobs -Data From Secondary Sources and Qualitativ...mentioning
confidence: 95%
“…16 In an Australian study based on the same cohort being analyzed in this paper, roughly three-quarters of emergent adults with an adolescent history of depression symptoms were employed in their late 20's. 15 There is an acknowledged dearth of studies on the impact of mental health problems in adolescence on the experience of work in adulthood. 17 A recent study showed that a history of childhood or adolescent mental health problems impacted the work functioning workers of young adult workers, in particular experiencing difficulties in meeting their work demands.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, the WHO estimates that 14% of 10–19‐year‐olds experience mental health conditions 14 . It has been previously shown that emergent adults with a history of mental health problems are less likely than their peers to have completed secondary education, and less likely to be in paid employment in the emergent adulthood period, including in Australia 15 . In absolute terms, however, most young people with a history of mental health problems, however, do find employment in emergent adulthood.…”
Section: Introductionmentioning
confidence: 99%